2004
DOI: 10.1111/j.0958-7578.2004.0489.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transfusion techniques: a systematic review of their efficacy

Abstract: Shortages of donor blood and fears of transmitted infections have prompted the use of a range of blood-sparing techniques in the peri-operative period. We conducted a systematic review of three techniques that involve the re-infusion of a patient's blood--pre-operative autologous blood deposit (PAD), acute normovolaemic haemodilution (ANH), and cell salvage (CS). We examined the effects of these interventions on the need for peri-operative allogeneic red blood cell transfusion and on clinical outcomes. Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 159 publications
4
139
0
8
Order By: Relevance
“…The use of autologous blood transfusion for elective orthopaedic surgery is decreasing, despite an overall upward trend in transfusion rates driven by an increase in allogeneic transfusions [7,45]. The decrease in this practice may be attributable to growing concerns regarding its cost-effectiveness and utility in patients without anemia [4,6,18,20], the possibility of iatrogenic anemia leading to increased overall transfusion rates [9,12,19], and some reports suggesting no differences regarding postoperative mortality and infection compared with allogeneic transfusions [9,30]. It therefore is possible that patients of higher socioeconomic status are asking for preoperative donation of blood to their own detriment, and, paradoxically, disadvantaged populations may not be receiving substandard care.…”
Section: Discussionmentioning
confidence: 99%
“…The use of autologous blood transfusion for elective orthopaedic surgery is decreasing, despite an overall upward trend in transfusion rates driven by an increase in allogeneic transfusions [7,45]. The decrease in this practice may be attributable to growing concerns regarding its cost-effectiveness and utility in patients without anemia [4,6,18,20], the possibility of iatrogenic anemia leading to increased overall transfusion rates [9,12,19], and some reports suggesting no differences regarding postoperative mortality and infection compared with allogeneic transfusions [9,30]. It therefore is possible that patients of higher socioeconomic status are asking for preoperative donation of blood to their own detriment, and, paradoxically, disadvantaged populations may not be receiving substandard care.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Much of the evidence suggesting a benefit from autologous transfusion is derived from methodologically poor studies with inadequate clinical outcomes. 15 Pre-operative Sufficient time should be allocated for the identification and treatment of anaemia, ideally in the setting of a surgical pre-assessment clinic. 14 Drugs that interfere with haemostasis should be discontinued wherever possible.…”
Section: Strategies For Reducing Blood Use In Surgical Patientsmentioning
confidence: 99%
“…This was associated with an increased IL-6 level in the blood drained in the early postoperative period. Carless et al (20) argued that autotransfusion should be applied carefully due to problems such as air emboli, infection, nephrotoxicity, metabolic hyperchloremic acidosis and disseminated intravascular coagulation. In the current study, two CSS patients reported shivering following re-transfusion and this was solved by ending re-transfusion.…”
Section: Discussionmentioning
confidence: 99%